A SEMIOTIC ANALYSIS: REFLECTION OF ETHICAL AND PSYCHOLOGICAL HEDONISM IN JANE AUSTEN’S NOVEL “EMMA” - Nuryuliana, Nuryuliana; Nur, Riola Haya (Faculty of Languages and Literature, Universitas Negeri Makassar, 2022)
This dissertation examines hedonism in 'Jane Austen's Novel Emma. The aims are to ascertain the hedonism, the varieties of hedonism, expressed by the novel's protagonist that the researcher want to impart to the readers. The study included qualitative research methods. The data for this study were derived from the